Effectiveness of an Affordable Toa Uzito Offloading Device for Healing Plantar Diabetic Foot Ulcer: A Matched Case–Control Clinical Study - Zulfiqarali G. Abbas; Roozbeh Naemi (International Wound Journal, 2026)
ABSTRACT Diabetic foot ulcers (DFUs) are difficult to manage in resource‐limited settings, where access to standard offloading devices is limited for healing of plantar diabetic foot ulcers. This is due to the cost, limited availability, and the need for specialised expertise. Toa Uzito is a low‐cost offloading device developed to address this gap. We evaluated the effectiveness of a low‐cost offloading device ( Toa Uzito ) in improving healing outcomes in patients with plantar ulcers. A matched case–control clinical study was conducted at a specialised diabetic foot centre in Dar es Salaam, Tanzania. Patients with a single plantar DFU were enrolled. Those treated with Toa Uzito were compared with matched controls who received standard care without offloading. Controls were matched based on age, body mass index, and diabetes duration. The primary outcome was time to complete ulcer healing. Healing were analysed using Kaplan Meier survival analysis and Cox regression. A total of 621 patients were included (128 intervention, 493 controls), with a mean follow‐up of 133.8 days. Ulcer healing was significantly better in the intervention group: 44.9% healed (versus 34.9% in controls) by 12 weeks, and increasing to 85% (versus 75.2% in controls) by 24 weeks. All patients in the intervention group healed, with a shorter mean healing time (125.7 vs. 137.5 days). Toa Uzito also demonstrated significantly superior healing efficacy compared with standard care after stratification by SINBAD classification (χ 2 = 71.2, p < 0.01) . The low‐cost Toa Uzito significantly improves healing rates and reduces time to healing. Its affordability and simplicity makes it an effective offloading strategy for promoting DFU healing in resource‐limited settings.